Learning of Multimedia-Based Physics Concept Applications to Improve Students’ Motivation and Science Process Skills - Jabaliah, Jabaliah; Adlim, Muhammad; Syukri, Muhammad; Evendi, Evendi (Jurnal Ilmiah Peuradeun, 2021)
Physics concept application is widely applied in daily life but students have a lack of knowledgeconcerning the concept of physics application. This research aimed to examine the motivation and skills of the scientific process through learning the concept of multimedia-based physics applications. This is experimental research, conducted on Year IX students of Islamic Senior High School. Samples were taken with purposive sampling techniques and divided into two groups of Mastery Learning Scores (MLS), MLS ≥ 70 and MLS< 70. Data were collected from Pre-test and post-test. The motivational data was presented through the category table, while the science process skills were analyzed using the Independent sample t-test. After the treatment, the initial motivation of the MLS class ≥ 70 was increased from 66.1% to 81.9%, while it was from 63% to 82.5% for the MLS class< 70. Besides, the final science process skillswere significantly different between the two classes, indicating byt count >t table 2.14 > 1.65. This study suggested that learning concepts of multimedia-based physics applications can improve student motivation in both classes, while the science process skills only affect the students of the MLS group ≥ 70.